Expression of reprogramming factors in mesenchymal stem cells isolated from equine umbilical cord Wharton’s jelly and amniotic fluid - RATHORE, N S; KASHYAP, S K; DEORA, ANUPAMA; KUMAR, PANKAJ; SINGH, J; TALLURI, T R (The Indian Journal of Animal Sciences, 2021)
Stem cells represent the most promising population for regenerative cell therapy and have gained much attention during the recent past. Mesenchymal stem cells (MSCs) are multipotent stem cells that can differentiate into trilineages. Like haematopoietic cells, mesenchymal cells have been shown to proliferate and form fibroblast-like colonies in vitro. Despite major progress in our general knowledge related to the application of adult stem cells, finding alternative sources for bone marrow MSCs has remained a challenge. A wide diversity of isolation procedures for mesenchymal stromal cells from various tissues of the placenta, umbilical cord and Wharton's jelly have been described for humans and other species. In this study, we isolated established umbilical cord Wharton’s jelly as a primary source for isolation of mesenchymal stem cells since it is a rich source of stem cells and no ethical concerns are involved. Equine umbilical cord Wharton’s jelly segments were collected during foaling time and digested enzymatically and cultured in-vitro in culture medium. In addition to the study of their morphology and colony forming units, the expression of reprogramming factors by the isolated MSCs were also studied. The isolated MSCs were observed to be plastic adherent, clonogenic and their morphology were polygonal, star shaped and fibroblast like. They revealed a strong expression of pluripotent stemness markers OCT-4, SOX-2, Nanog and KLF-4. From the current study, it can be concluded that Wharton's jelly is a rich source of stem cells with stemness properties expressing the reprogramming factors and mesenchymal like morphology and could be used as an alternate for the bone marrow derived mesenchymal stem cells for cell based regenerative therapies.